Konsep Lanskap Linguistik pada Papan Nama Jalan Kerajaan (Râjamârga): Studi Kasus Kota Yogyakarta - Erikha, Fajar (UI Scholars Hub, 2018)
Linguistic landscape (LL) refers to a set of linguistic objects which signifies a public space (Ben-Rafael, Shohamy et al., 2006). This concept encompasses a number of topics such as social, political, cultural, and economic ones. Using the concept of LL, the author examined the names of the main streets (râjamârga) around the Yogyakarta Palace in terms of their function as the identifiers of place names (informational function) and as carriers of certain messages (symbolic function). In order to generate comprehensive results, the author used qualitative approach through the analysis of visual data (photographs) of street name plates. The findings reveal two functions of linguistic landscape which is established by street name plates. The first is informational function, namely to refer to geographical places and to the social space of the Javanese which are presented as a single ethnic group, while the orthographic use of hanacaraka asserts language boundary. The second is symbolic function, namely to convey a collection of meanings (according to the philosophy of Paraning Dumadi), to delineate Javanese as an ethnic group, to designate Javanese as the native language of the local people, to indicate a strong link between governmental powers and place naming practices, and even to serve economic purposes by attracting tourists to Yogyakarta.